2003
DOI: 10.1515/znc-2003-11-1202
|View full text |Cite
|
Sign up to set email alerts
|

Externally Accumulated Flavonoids in Three Mediterranean Ononis Species

Abstract: The Mediterranean Ononis species, O. fruticosa, O. natrix subsp. ramosissima and O. tridentata, have been analyzed for their exudate flavonoids. More than 20 flavonoid aglycones were identified, some of which are rather rare natural compounds. One of them, namely hypolaetin-8,3Ј,4Ј-trimethyl ether, had been found only once before. The results are presented in a table along with literature data, and the chemotaxonomic impact of the flavonoid patterns is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…Because the respective compounds produced by both saxifrage and soybean (43,44) belong to different flavonoid subclasses than the basil and mint flavones, the independent origins of analogous catalytic capacities are not quite unexpected. It remains intriguing what type of catalyst mediates the 6-hydroxylation of the same flavonoid subclass, the flavones, in distantly related species and genera accumulating identical compounds, such as, for example, Tamarix, Citrus, Ononis, and others (7,45,46). So far, our BLAST searches of Citrus sinensis and Citrus clementina genomes and EST collections, as well as Helianthus annuus ESTs (using Phytozome and NCBI GenBank TM online tools) only yielded protein sequences with less than 55% identity to CYP82D33, which precludes function prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Because the respective compounds produced by both saxifrage and soybean (43,44) belong to different flavonoid subclasses than the basil and mint flavones, the independent origins of analogous catalytic capacities are not quite unexpected. It remains intriguing what type of catalyst mediates the 6-hydroxylation of the same flavonoid subclass, the flavones, in distantly related species and genera accumulating identical compounds, such as, for example, Tamarix, Citrus, Ononis, and others (7,45,46). So far, our BLAST searches of Citrus sinensis and Citrus clementina genomes and EST collections, as well as Helianthus annuus ESTs (using Phytozome and NCBI GenBank TM online tools) only yielded protein sequences with less than 55% identity to CYP82D33, which precludes function prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavonoid secretion affects the surrounding microflora in the rhizosphere (Weisskopf et al, 2006), attracts mutualistic microorganisms such as nitrogen-fixing bacteria, and enhances defense responses to pathogens (Paiva, 2000;Dakora and Phillips, 2002). Flavonol glycosides have been detected in the cell wall fraction of Scots pine (Pinus sylvestris) needles (kaempferol 3-glucoside; Schnitzler et al, 1996) and Chrysosplenium americanum (polymethylated flavonol glucosides; Ibrahim et al, 1987), while flavonoid aglycones, including flavones and flavonols, have been detected in exudates of numerous species (Valant-Vetschera and Wollenweber, 2001;Wollenweber et al, 2003).…”
mentioning
confidence: 99%
“…Furthermore, purification using PPC and sephadex LH-20 resulted in the isolation of six compounds identified on the basis of spectral data (UV, NMR, EI-MS) as well as comparison with published data (Wollenweber et al, 2003;Wallage, 1971;Mesquita et al, 1986;Lin et al, 2006;Bai et al, 2011;Nagao et al, 2002;Marder et al, 1996), and identified as five flavones (1-5) and one phenolic acid (6). Acerosin (1) was identified for the first time in genus Achillea.…”
Section: Discussionmentioning
confidence: 89%